The cruciform faculty : the making of a Christian professor - Heinemann, Mark H.; Estep, James Riley, Jr; Maddix, Mark Amos; Esqueda, Octavio Javier (Emerald Publishing Limited : Information Age Publishing Inc., 2017)
How do Christian higher education institutions orient new faculty members to their role on a Christian campus? How do they lead faculty members toward a deeper understanding of the Christian dimension of their place in higher education? Bible Colleges, Christian Universities, and Seminaries need a resource that can be provided to faculty members or be used in faculty development discussions.This book is designed to serve as just such a resource. It provides a clear and concise portrait of the general role of faculty from a distinctively evangelical Christian perspective. We use the metanarrative of being formed by the cross to describe the 'cruciform' role of professors as teachers in the classroom, mentors to the students, scholars within the academy, and servants of the church and community. Each chapter will have personal and group reflection questions and exercises to aid in application.